POTENSI PREBIOTIK POLISAKARIDA LARUT AIR UMBI GEMBILI (Dioscorea Esculenta L) SECARA IN VITRO - Herlina Herlina; Harijono Harijono; Achmad Subagio; T. Estiasih (Faculty of Agricultural Technology, University of Jember, 2011)
Water soluble polysaccharides (WSP) from gembili tuber is one water soluble food fiber whose existence in the gembili tuber in a free state or bound to proteins. Therefore, to increase the purity of the WSP in the extraction process is required deproteinase. The WSP with different levels of purity will affect its potential as a prebiotic. The purpose of this study was to determine the potential of WSP as a prebiotic and gembili tuber deproteinase effect on the growth of lactic acid bacteria (BAL). This research was conducted by covering the extraction stage WSP gembili tuber using distilled water (WSPc) and extraction of gembili tuber WSP using distilled water, followed by the Aspergillus oryzae protease with 0.05% (WSPd), WSP chemical testing, and testing of potential prebiotic WSP gembili tuber in vitro at various concentrations (1%, 2%, and 3%) with BAL indicators probiotics (Lactobacillus bulgaricus, Streptococcus thermophilus, Bifidobacterium longum), as well as testing the pH and acid that accumulates in the BAL growth media. The results showed that the WSPc and WSPd of gembili tubers potentially as a prebiotic for S. thermophilus, L. bulgaricus, and B. longum. WSPd more effective as a carbon source for growth of B. longum, use WSPd 2% as an energy source for growth of B. longum replace glucose, the amount of total growth in B. longum amounting to 1.76 x 109 CFU / ml. Based on data of the growth media pH and acid production accumulated in BAL growth media, using glucose as a carbon source (control) is better for growth of S. thermophilus and L. bulgaricus, whereas WSP gembili tubers (WSPc and WSPd) is better as a carbon source for B. longum. Keywords: gembili tuber, water-soluble polysaccharide (WSP), deproteinse, prebiotics, probiotics